Tolerance as a Way of Constructing a SocialCultural Space - Pirumyan, Tatevik (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
The article discusses tolerance as a way of constructing socialcultural space. Tolerance can serve as a main factor for modelling a society. Globalization influences all aspects of modern social reality. Crosscultural communication becomes inseparable of social communication, its main concepts (the opposition ownother, conflict, stereotypes, tolerance) getting the new content under sociocultural specific nature. With the increasing migration, society faces a serious problem of socialcultural tolerance towards migrants.
Keywords: tolerance, construction of social and cultural space, social norm, inter-ethnic tolerance, ethnic identity, social communication, intolerance